Impact of the COVID‐19 pandemic on older adults mental health services: A mixed methods study. (9th July 2021) - Bhome, Rohan; Huntley, Jonathan; Dalton‐Locke, Christian; San Juan, Norha Vera; Oram, Sian; Foye, Una; Livingston, Gill
Abstract: Objectives: The COVID‐19 pandemic has had a significant impact on older adults mental health care. Our study aimed to explore staff perspectives on key challenges and innovations in order to help inform the delivery of older adults mental health care in subsequent waves of the pandemic. Methods: A mixed methods online questionnaire developed by National Institute for Health Research Mental Health Policy Research Unit was used to gather staff perspectives on their challenges at work, problems faced by service users and their carers, and sources of help and support. Descriptive statistics were used for quantitative analysis and descriptive content analysis for qualitative analysis. Results: 158 participants, working in either community or inpatient settings, and from a range of professional disciplines, were included. For inpatient staff, a significant challenge was infection control. In the community, staff identified a lack of access to physical and social care as well as reduced contact with friends and families as being challenges for patients. Remote working was seen as a positive innovation along with COVID‐19 related guidance from various sources and peer support. Conclusion: Our study, with a focus on staff and patient well‐being, helps to inform service development for future waves of the pandemic. We discuss measures to improve infection control in inpatient settings, the role of voluntary organisations in supporting socially isolated community patients, the need for better integration of physical and mental health services at an organisational level, and the importance of training staff to support patients and their families with end of life planning. Key points: This is the first study to elicit the views of staff about the impact of COVID‐19 on older adult mental health services. In inpatient services, implementing effective infection control measures was difficult whilst in the community the loss of usual support networks was seen as a challenge for patients. Clear protocols for infection control may benefit staff and patients in inpatient settings. In the community, there needs to be close liaison between mental health, social care and voluntary services. Across all settings there needs to be better consideration of end of life planning. Future research should ascertain patients and carer's perspectives on the impact of the pandemic on mental health services that they have received.